The credit programme of the Chilalo Agricultural Development Unit (CADU) IN Ethiopia - Holmberg, Johan (Washington, D.C. : Agency for International Development Department of State, 1972)
This book shows how Ethiopia attached importance to lending facilitates to small farmers
Includes bibliographical references.
mf 23/01/2019
Loans
Keywords: Agricultural credit